2024
DOI: 10.1136/jnnp-2023-332457
|View full text |Cite
|
Sign up to set email alerts
|

Risk of stroke with different levels of leisure-time physical activity: a systematic review and meta-analysis of prospective cohort studies

Federico De Santis,
Michele Romoli,
Matteo Foschi
et al.

Abstract: BackgroundLeisure-time physical activity (LTPA) protects against vascular diseases. Whether and to what extent different levels of LTPA, including lower ones, benefit stroke prevention is still unclear.MethodsWe searched prospective cohort studies, indexed on PubMed and Scopus, published in English up to 22 April 2023, that investigated, in a general healthy population, the relationship between different predefined LTPA levels, compared with inactivity, and the risk of any type of stroke. We applied random eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
1
1
Order By: Relevance
“… 33 A recent systematic review and meta‐analysis of prospective cohort studies investigating vascular diseases found that physical activity, “even at the lowest levels,” was beneficial for stroke and vascular disease prevention. 34 This is in line with our findings that both MVPA (min/d) and adherence to the guideline MVPA threshold (min/wk) were associated with a reduction in CeVD risk, with the latter conferring a stronger protective effect. 35 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 33 A recent systematic review and meta‐analysis of prospective cohort studies investigating vascular diseases found that physical activity, “even at the lowest levels,” was beneficial for stroke and vascular disease prevention. 34 This is in line with our findings that both MVPA (min/d) and adherence to the guideline MVPA threshold (min/wk) were associated with a reduction in CeVD risk, with the latter conferring a stronger protective effect. 35 …”
Section: Discussionsupporting
confidence: 91%
“…It is unsurprising that no significant association was found between SB and CeVD risk, as evidence supporting the value of reducing or replacing SB is inconclusive. 34 Alternatively, the negative influence of SB may be most noticeable in individuals who spend the least amount of time in MVPA. 35 …”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, another meta-analysis of 752,050 follow-up participants also found that all levels of leisure-time physical activity were beneficial in preventing stroke. 19 Notably, our study did not find that all kinds of physical activity could prevent stroke, possibly due to the exclusion of occupational physical activities.…”
Section: Discussioncontrasting
confidence: 57%